2014
DOI: 10.17576/pengurusan-2014-41-01
|View full text |Cite
|
Sign up to set email alerts
|

Risk-Adjusted Performance of Malaysian Real Estate Investment Trust Funds

Abstract: This study evaluates performance and risk features of Malaysian REIT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In Malaysia, there are several previous research about REITs. For example, the result of the risk-adjusted performance analysis of M-REITs from the year 2007 to 2012 suggested that all beta values were smaller than one (less volatile than the overall market) and that the total risk of REIT funds was linked to the unsystematic risk component (Low & Johari, 2014). In spite of conventional REITs, Islamic REIT (I-REIT) is one of Malaysian researchers' focus since it is favourable to compare with conventional REITs, according to the efficiency ratios of Return of Asset (ROA) and Return of Equity (ROE) (Khairulanuwar & Chuweni, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In Malaysia, there are several previous research about REITs. For example, the result of the risk-adjusted performance analysis of M-REITs from the year 2007 to 2012 suggested that all beta values were smaller than one (less volatile than the overall market) and that the total risk of REIT funds was linked to the unsystematic risk component (Low & Johari, 2014). In spite of conventional REITs, Islamic REIT (I-REIT) is one of Malaysian researchers' focus since it is favourable to compare with conventional REITs, according to the efficiency ratios of Return of Asset (ROA) and Return of Equity (ROE) (Khairulanuwar & Chuweni, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Real estate investment trust (REIT) is an investment vehicle or a unit trust scheme that invests in income-producing properties, which range from office or commercial buildings, shopping malls, industrial properties, resorts or hotels, healthcare facilities to specialty-built buildings (Chuweni, Ali, Ismail & Ahmad, 2015;Low & Johari, 2014). REIT market started to grow in Asia since the first decade of the 21st century (Newell et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…With interest in and demand for, REIT investment growth, information on the performance of REITs is becoming increasingly important to potential investors (Soo-Wah and Johari, 2014). Further, the outlook for investment yields is one of the critical uncertainties facing real estate investors (Hollies, 2007).…”
Section: Introductionmentioning
confidence: 99%